Quintus Smyrnaeus: Transforming Homer in Second Sophistic Epic - Baumbach, Manuel; Bär, Silvio (Millennium-Studien / Millennium Studies, 2012)
The "Events after Homer", described by Quintus Smyrnaeus in the third century AD in his Greek epic Posthomerica, are an attempt to bridge the gap between the Iliad and the Odyssey , and to combine the various scattered reports of the battle for Troy into a single tale: the fate of Achilles, Ajax, Paris and the Amazon Penthesileia, the intervention of Neoptolemos and the story from the Trojan horse to the destruction of the city. The volume presented here summarizes the results of the first international conference on Quintus Smyrnaeus.